OECD domestic support in and developing countries - Betina Dimaranan; Thomas Hertel; Roman Keeney (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
An AGE model with detailed farm supply and substitution relationships is used to analyze impacts of OECD domestic support reform on developing economy welfare. Stylized simulations indicate reforms best suited for reducing trade distortions with least impact on farm incomes. Comprehensive reforms result in welfare losses for LDCs and large declines in OECD farm incomes. Shifting from market price support to land-based payments designed to maintain farm incomes results in increased welfare for most developing countries. LDCs should focus on improved market access to OECD economies while permitting said economies to continue domestic support payments not linked to output/variable inputs.
Keywords: D58; F13; F14; O19; Q17; 330; domestic support; OECD; developing countries; agricultural trade; WTO; Agraraußenhandel; Agrarprotektionismus; OECD-Staaten; Entwicklungsländer